The Facial Expressions Determine the Character of 5-Year-Old Children: A Study of Semiotics, Psychology, and Nonverbal Communication - Aryana, Suhud (IKIP Siliwangi, 2025)
This study aims to examine the relationship between facial expressions and the character of five-year-old children through the perspectives of semiotics, psychology, and nonverbal communication. A child's facial expressions are considered important indicators in revealing their emotions and personality. Using a semiotic approach, this research analyzes the nonverbal signs present in the child's facial expressions, which can provide a deeper understanding of their nature and character. In the framework of psychology, facial expressions are seen as manifestations of emotional states related to the child's personality type, such as melancholic, sanguine, choleric, or phlegmatic. Additionally, the aspect of nonverbal communication in this study focuses on how children interact through facial expressions, indicating their level of concentration, assertiveness, or calmness. Based on the analysis of nonverbal signs, semiotic systems, and personality types, this study concludes that the child in the image shows characteristics of a choleric personality, with a determined facial expression, a defensive posture (arms crossed), and a focused gaze, suggesting dissatisfaction or resistance. Furthermore, other nonverbal signs also indicate sanguine traits with a cheerful expression and relaxed body, as well as melancholic traits with a serious expression and introspective tendency. The combination of these signs indicates that the child possesses a dominant, social, and sensitive character, with a tendency towards deep emotional feelings.